In-silico analysis of ribbon sea lettuce (ulva reticulata) proteins for potential bioactive peptides - Tabaog, Timothy James A. (College of Home Eonomics, University of the Philippines Diliman, 2024)
There has been a significant expansion in the development of therapeutic peptides and the search for natural sources of bioactive peptides (BAP). This growth is fueled by the numerous applications of BAPs in functional foods, including their potential to address health concerns like metabolic and cardiovascular diseases. Ribbon Sea lettuce (Ulva reticulata), a green seaweed species in the Philippines more commonly known as “lumot”, with a high protein content of 21.06% on a dry basis, emerges as a promising candidate for bioactive peptide (BAP) production. Despite this potential, no previous studies have investigated U. reticulata proteins as BAP precursors. In this study, 13 U. reticulata proteins were selected as potential precursors of BAPs using in silico approach. It was found that the most potential bioactivity was dipeptidyl peptidase-IV (DPP IV) inhibitory and angiotensin-I converting enzyme (ACE) inhibitory activities across all the enzymes analyzed. Digestive enzymes such as Trypsin, Chymotrypsin, and Pepsin, industrial proteases such as Thermolysin and plant proteases such as Papain, and Stem Bromelain were used for in-silico proteolysis. Stem bromelain and was found to be more effective in terms of the release of fragments with a given activity. RuBisCO proteins also had the best potential to release BAPs. The study suggests that U. reticulata can serve as a potential source of BAPs and these findings can provide a basis for future in-vitro and in-vivo study of BAPs from U. reticulata proteins.